Age-Related Changes in Bone Remodelling and Structure in Men: Histomorphometric Studies. (1st November 2011) - Compston, Juliet
Abstract : Histomorphometric studies of the age-related changes in bone remodelling and structure in men are relatively sparse and mainly limited to the iliac crest. The available data indicate that loss of trabecular bone is predominantly due to decreased formation at the level of individual bone remodelling units and that an increase in remodelling rate does not play a major role. The main structural consequence of the changes in bone remodelling is trabecular thinning. In cortical bone, an age-related reduction in cortical width and increase in porosity have been demonstrated at several skeletal sites. However, the alterations in bone remodelling responsible for these changes remain to be established.